ANALISIS KUALITAS BUTIR SOAL PENILAIAN AKHIR SEMESTER GASAL TAHUN 2021/2022 MENGGUNAKAN ITEMAN DI SMP NEGERI 1 KAMBERA - Marambaawang, Damianus; Bano, Vidriana Oktoviana; Hada Enda, Riwa Rambu (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
In the data from the odd semester final exam results for the 2021/2022 school year, there are many students at SMPN 1 Kambera who score below the KKM standard. Referring to this, this study aims to evaluate the characteristics of each item of questions used in the final exam of the semester using several predetermined criteria. This study applies a quantitative descriptive method. The sample taken is class VIIID. The results of the analysis using ITEMAN show that 25% of the items are invalid and 75% of the items are valid. In addition, its reliability reaches a high level of